Pengaruh Pertumbuhan Penjualan, Current Ratio, Debt To Equity Ratio, Ukuran Perusahaan, Dan Perputaran Persediaan Terhadap Profitabilitas Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di BEI - Ninta Katharina; Graccella Graccella; Andy Putra; Vinny Vica Yoanna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
Returnl Onl Assetl (ROA) is one of the variable which is used to see the capability of a company in order to obtained profit from the assets that it owns. The purpose of this research is to see the effect of Sales Growth, Current Ratio, Debt to Equity Ratio, Firm Size, and Inventory Turnover against Return On Asset, This type of research is quantitative descriptive with secondary data sources, selection of the sample in this research is using purposive sampling method and this research test method is using multiple linear regression analysis method. The amount of population in this research is 84 consumer goods industry sector companies that registered in Indonesia Stock Exchange (IDX) in 2017-2019. Based on the research results we can conclude that Growth Sales, Current Ratio, Debt to Equity Ratio, Firm Size, and Inventory Turnover simultaneously have a significant and positive effect against Returnl Onl Asset. Meanwhile, only Debt to equity Ratio that partially has a positive effect against Return On Asset, while Growth Sales, Current ratio, Firm Size, and Inventory Turnover have no significant effect against Return On Asset. Keywords : Growth Sales, Current Ratio, Debt to Equity Ratio, Firm Size, Inventory Turnover.